2018
DOI: 10.1515/msp-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescence Properties of ZrO2:Gd3+, RE3+(RE = Sm3+ ,Er3+) Phosphors

Abstract: In the present study, ZrO2co-doped with Gd3+/Sm3+and Gd3+/Er3+ions have been synthesized using Pechini method. Phase composition, morphology and photoluminescence properties of the synthesized phosphors were investigated by using X-ray powder diffraction (XRD), differential thermal analysis/thermal gravimetry (DTA/TG), scanning electron microscopy (SEM) and photoluminescence spectrofluorometer (PL). After heating at 1200 °C, XRD revealed that the phosphors were crystallized as monoclinic and tetragonal multiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The dissimilarity in the intensity of TL for doped and undoped ZrO 2 is explained as due to the difference in the number of the luminescence centre. We argued that the rare‐earth dopants [71, 81, 82] increase oxygen vacancies [83] and thus the number of luminescence centres rises [42, 77, 84–86].…”
Section: Discussionmentioning
confidence: 99%
“…The dissimilarity in the intensity of TL for doped and undoped ZrO 2 is explained as due to the difference in the number of the luminescence centre. We argued that the rare‐earth dopants [71, 81, 82] increase oxygen vacancies [83] and thus the number of luminescence centres rises [42, 77, 84–86].…”
Section: Discussionmentioning
confidence: 99%
“…13 Various studies have been conducted in recent years to explore the photoluminescence properties of ZrO 2 doped with different ions such as Sm 3+ , Er 3+ , Eu 3+ , Tb 3+ , and Ti 4+ ions. 14–16 The ML properties of ZrO 2 :Ti have also been noted. Akiyama et al 17 observed strong green light in the ZrO 2 :Ti 4+ phosphor, and realized full recovery of ML intensity under UV irradiation.…”
Section: Introductionmentioning
confidence: 94%